Viruses, immunity and evolution. (October 2022) - Melkikh, Alexey V.
Abstract: In this article, the evolution of viruses is analyzed in terms of their complexity. It is shown that the evolution of viruses is a partially directed process. The participation of viruses and mobile genetic elements in the evolution of other organisms by integration into the genome is also an a priori directed process. The high variability of genomes (including the genes of antibodies), which differs by orders of magnitude for various viruses and their hosts, is not a random process but is the result of the action of a molecular genetic control system. Herein, a model of partially directed evolution of viruses is proposed. Throughout the life cycle of viruses, there is an interaction of complex biologically important molecules that cannot be explained on the basis of classic laws. The interaction of a virus with a cell is essentially a quantum event, including selective long-range action. Such an interaction can be interpreted as the "remote key-lock" principle. In this article, a model of the interaction of biologically important viral molecules with cellular molecules based on nontrivial quantum interactions is proposed. Experiments to test the model are also proposed.